Robust complete synchronization control design for non‐collocated nonlinear master–slave system over delayed communication network - Yang, Yana; Jiang, Huixin; Li, Junpeng; Hua, Changchun (International journal of robust and nonlinear control, 2023)
In this article, a predictor‐based robust synchronization control scheme is proposed for a non‐collocated nonlinear master–slave system with any large networked communication time delays. In contrast to traditional collocated teleoperation systems, enhanced flexibility, and operation capacity will be obtained under the non‐collocated system structure in this article. Yet, due to the introduced input delays, existing control strategies for teleoperation systems are no longer applicable. Aiming at this problem, the terminal sliding mode (TSM) admittance control approach is proposed for the master robot to improve system transparency by receiving the contact force from the slave robot to the local side, first. Moreover, complete position synchronization performance is realized by developing a predictor‐based TSM control method for the slave robot while the closed‐loop system is subject to time‐variant large delays. It is mathematically proved that the synchronization errors between the master and the slave will converge to zero completely in finite time by compensating the effect of time delays. Finally, numerical simulations and comparisons are executed to illustrate the superior performance of the posed control algorithms.